Code Switching and Code Mixing in Film Imperfect - Amriani, Annisa; Sahayu, Wening; Faizal, Abdul Azis (EDUPEDIA Publisher, 2023)
In ordinary life, we frequently speak in a language that is not understood by others. When communicating, we frequently employ language switching or merging, also known as code switching and code mixing. Which seeks to make the interlocutor more understandable. Code switching and code mixing are used in today’s works of art, particularly films, to communicate amongst actors in their own films. This is done not just as a trick, but also because there is a lot of terminology from foreign languages that has been assimilated into Indonesian and is used more frequently. So the purpose of this research is to look at and learn about the many sorts of code switching and code mixing in the IMPERFECT film, as well as the rationale for using code switching and code mixing in the IMPERFECT film.